How the design of an organizational context helps to attain contextual ambidexterity - Klaus Möller; Flavia Schmid; Theresa Maria Seehofer; Philipp Wenig (Schmalenbach Journal of Business Research (SBUR), 2022)
This study empirically investigates the relationships of control levers (belief and boundary systems, Simons 1995) and control context (social and performance management context, Gibson and Birkinshaw 2004) with contextual ambidexterity and firm performance. Based on cross-sectional survey data from 198 listed companies in Austria, Germany, and Switzerland, a structural equation model is used to test the hypothesized relationships. We find that the emphasis on formal boundary systems and an informal social context are positively related to contextual ambidexterity, which positively affects firm performance. In contrast, belief systems and performance management context do not influence contextual ambidexterity. Further, we find no support for dynamic tensions, neither between the two control levers nor in the control context.
Keywords: 650; Contextual Ambidexterity; Control System; Organizational Context; Resilience